MODELAGEM MATEMÁTICA: ARTICULAÇÕES ENTRE A PRÁTICA E PROPOSTAS CURRICULARES OFICIAIS - Kovalski, Lenilton (2016)
This thesis presents a survey guided by the question: In practice, the Mathematical Modeling contemplates points presented in official curriculum proposals? From this issue, seeks to highlight possible links between the mathematical modeling in practice and official curriculum documents, favorable to working with this methodology, providing theoretical support for teachers who have adopted, or plan to adopt, the mathematical modeling in their teaching practices, and are among some of the obstacles to this, the need to break the traditional way of how the curriculum is worked and, often, the non-acceptance of this methodology by the school community who does not realize immediately the potential of Mathematical Modeling. For the lifting of these joints the present work brings a discussion of the Mathematical Modeling in Mathematics Education, a brief description of the National Curriculum Parameters (PCN) and the draft of the Curriculum Common National Base (BNCC) of focused way to Mathematics discipline in final years of elementary school. Two practices with mathematical modeling, performed by the author, are also described, and finally, the joints identified between the mathematical modeling and the official curriculum documents, PCN and BNCC are listed from the three pillars that support the research: the theoretical framework on Mathematical Modeling; the official curriculum documents that were selected for this study, PCN and BNCC; and the two experiments with mathematical modeling reported. As a result of the interpretations of this research, it is clear that multiple joints can be listed among the Mathematical Modeling in practice and two official curriculum documents, PCN and BNCC, which are favorable to working with the methodology in question, and that the adoption of Mathematical Modeling for basic education teachers can enable an improvement in the teaching and learning of mathematics today, as legitimately proposals found in the NCP and BNCC.